Synergistic optimization of photothermoelectric performance of a perovkite/graphene composite. Issue 3 (1st February 2022) - Li, Mengyao; Tang, Xin; Wang, Silei; Li, Tengteng; Li, Jitao; Zhao, Hongliang; Li, Qingyan; Wang, Qi; Zhang, Yating; Yao, Jianquan
Abstract: Previous studies have shown that graphene's particular optical and electrical properties endow it with powerful potential in infrared (IR) photodetection. However, the responsivity of detectors is limited by the weak absorption and high thermal conductivity of graphene. Here, we report synchronous laser reduction to fabricate the intercalated MAPbI3 /RGO composite to improve the photothermoelectric (PTE) performance and break through the barrier of responsivity of graphene photodetectors at room temperature. Combined with experimental phenomena and theoretical analysis, the introduction of MAPbI3 improved the fundamental thermoelectric properties of the composite, such as absorption coefficient, thermal conductivity, Seebeck coefficient, and thermal sensitivity index, etc. The MAPbI3 /RGO detector shows significant performance breakthroughs in sensitivity, noise-equivalent power (NEP) in the IR region, responsivity as high as 44.24 mV/W, and noise-equivalent power of 7.17 nW/√Hz at 980 nm. The fast and low-cost fabrication of inserting perovskite into multilayer graphene offers opportunities to decouple the carrier and phonon transmission in materials, thus promising for developing high-performance PTE photodetectors.